Physiology as a Lingua Franca for Clinical Machine Learning - Sarma, Gopal P. (Patterns (N Y), 2020)
The intersection of medicine and machine learning (ML) has the potential to transform healthcare. We describe how physiology, a foundational discipline of medical training and practice with a rich quantitative history, could serve as a starting point for the development of a common language between clinicians and ML experts, thereby accelerating real-world impact.